The “Blusukan” Leadership Style of Elementary School Principals in Kota Lubuklinggau : What Lessons Can Be Learned? - Ahmad Gawdy Prananosa; Donni Pestalozi; Rudi Erwandi; M. Rusni Eka Putra (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to reveal the phenomenon of elementary school principals in Kota Lubuklinggau engaging in blusukan leadership. The research employed a qualitative approach with a phenomenology method. The subjects involved were school principals, teachers, and school staff. The data were collected using observations, interviews, and documentation. The obtained data were then analyzed using Miles and Huberman’s interactive models in the following steps: data collection, reduction, display, and conclusion drawing/verification. The results indicated that: 1) the concept of blusukan was performed by the elementary school principals through their willingness to directly supervise the working conditions of their subordinates to get real and accurate information from various sources; such information might be taken as consideration when making a decision; 2) The blusukan leadership style was implemented by encouraging subordinates, hearing and valuing their views, and sustaining close bonds between leaders and subordinates; 3) communication made by leaders was clear and not ambiguous, also easy to understand language, so subordinates can accept messages accurately, 4) due to the other vital obligations of school principals, the blusukan style should not be executed on a daily basis. Blusukan could also be done on the fly to check on subordinates while working. In this digital age, leaders could also utilize technology to support their blusukan by controlling the jobs of their subordinates through CCTV media.